Integration of Artificial Intelligence Technology as an Innovation in Learning Resources in Islamic Education - Annisa Maulida Setiawan (Universitas Nurul Jadid, 2026)
This article aims to analyze the opportunities and challenges of integrating artificial intelligence (AI) tools as learning resources in Islamic education. The rationale behind this research arises from the demands for learning innovation in the digital era, which requires the use of AI to improve educational efficiency and relevance. This analysis aims to identify AI's potential to assist with learning adjustments, improve digital literacy, and expand access to learning resources, while also considering existing constraints such as teacher preparedness and infrastructure limitations. The method used was literature review. Data collection was conducted through secondary data collection. Secondary data was obtained from various sources, including scientific articles, journals, books, and relevant research reports. The study's findings indicate that AI integration offers significant potential for enriching learning methods and supporting personalized learning, access to learning resources, and increasing the effectiveness of digital-based learning. Within Islamic education, AI can help teachers design more interactive materials and provide learning simulations. However, careful implementation strategies are required to avoid conflicting with Islamic educational principles.